2013
DOI: 10.1002/anie.201307144
|View full text |Cite
|
Sign up to set email alerts
|

3‐Methyl‐4‐oxa‐5‐azahomoadamantane: Alkoxyamine‐Type Organocatalyst for Alcohol Oxidation

Abstract: Strong, silent type: A novel alkoxyamine‐type organocatalyst has been discovered for alcohol oxidation (see scheme). The alkoxyamine exhibits a high catalytic activity for the oxidation of alcohols to afford the corresponding carbonyl compounds in high yield by oxidative transformation into an oxoammonium ion, which is proposed to serve as an active species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…[34] This method was based on prior work utilizing the same family of precatalysts for simple oxidations and the kinetic resolution of activated alcohols. [35] On the basis of careful spectroscopic analysis and independent isolation experiments, the active catalytic species was identified as a pair of chlorinated oxoammonium ions ( 25a and 25b ) generated from the reaction of 24 with trichloroisocyanuric acid (TCICA).…”
Section: Catalyst–catalyst Cation–π Interactionsmentioning
confidence: 99%
“…[34] This method was based on prior work utilizing the same family of precatalysts for simple oxidations and the kinetic resolution of activated alcohols. [35] On the basis of careful spectroscopic analysis and independent isolation experiments, the active catalytic species was identified as a pair of chlorinated oxoammonium ions ( 25a and 25b ) generated from the reaction of 24 with trichloroisocyanuric acid (TCICA).…”
Section: Catalyst–catalyst Cation–π Interactionsmentioning
confidence: 99%
“…On the base of previous literatures reported, [40–42] a plausible reaction mechanism for the 1‐Me‐AZADO/MPNs catalyzed oxidation of alcohols was proposed and illustrated in scheme 2. An initial one electron oxidation of the supported catalyst affords oxoammonium cation ( A ) in the presence of NaClO and KBr.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that the recyclable performance of the catalyst was strongly dependent on the activity of substrate, which might be similar to that of the previous report. [34] On the base of previous literatures reported, [40][41][42] a plausible reaction mechanism for the 1-Me-AZADO/MPNs catalyzed oxidation of alcohols was proposed and illustrated in scheme…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Unfortunately, the method was faded away, since bromine was a toxic, dangerous, and environmentally harmful reagent. In recent years, several oxidation systems with the assistance of bromide have been developed.…”
Section: Introductionmentioning
confidence: 98%